Mehamami Modus dan Pencegahan Penipuan Penggalanganan Donasi Online : Understanding Modes and Prevention of Online Donation Fraud - Giri Lumakto; Nur Kumala Dewi (Jurnal Bimas Islam, 2021)
The nature of philanthropy culture is inseparable from Indonesian society. By donating Indonesia ranks first as the country in terms of generosity according to the World Giving Index 2020 report. In the time of the Covid-19 pandemic, digital donations became a beneficial solution for need of giving donation. According to the GoPay Digital Donation Index 2020 report, interest in online donations is quite high among Millennials. However, from the increase of online donations, there are people who abuse it. There are three common modes that are done, namely; 1) using fake photos, 2) using the name of an official institution, and 3) pretending as a public figure. To prevent getting caught up in fake donation fraud there are 6 steps that can be done. This article will discuss both the mode of fraud and its preventive measures.